ILRI Genotype by Sequencing (GBS) data on global collections of Napier Grass - Muktar, Meki; Jones, Chris (2023)
The data set contains high density genome-wide SNP and SilicoDArT markers on 574 Napier grass genotypes conserved in five international institutes - the ILRI forage genebank, EMBRAPA, KALRO, ICRISAT, and USDA-ARS. Additional progeny plants produced from the ILRI collection's seed-setting Napier grass genotypes are also included. The markers data are useful for genetic diversity analysis, marker assisted selection, genomic selection, and QTL identification in Napier grass.